Cost of Capital : Applications and Examples - Pratt, Shannon P. (Wiley finance series., 2014)
A one-stop shop for background and current thinking on the development and uses of rates of return on capital Completely revised for this highly anticipated fifth edition, Cost of Capital contains expanded materials on estimating the basic building blocks of the cost of equity capital, the risk-free rate, and equity risk premium. There is also discussion of the volatility created by the financial crisis in 2008, the subsequent recession and uncertain recovery, and how those events have fundamentally changed how we need to interpret the inputs to the models we use to develop the.